Altered Brain Expression of Insulin and Insulin-Like Growth Factors in Frontotemporal Lobar Degeneration: Another Degenerative Disease Linked to Dysregulation of Insulin Metabolic Pathways. (May 2019) - Liou, Connie J.; Tong, Ming; Vonsattel, Jean P.; de la Monte, Suzanne M.
Background: Frontotemporal lobar degeneration (FTLD) is the third most common dementing neurodegenerative disease with nearly 80% having no known etiology. Objective: Growing evidence that neurodegeneration can be linked to dysregulated metabolism prompted us to measure a panel of trophic factors, receptors, and molecules that modulate brain metabolic function in FTLD. Methods: Postmortem frontal (Brodmann's area [BA]8/9 and BA24) and temporal (BA38) lobe homogenates were used to measure immunoreactivity to Tau, phosphorylated tau (pTau), ubiquitin, 4-hydroxynonenal (HNE), transforming growth factor-beta 1 (TGF-β1) and its receptor (TGF-β1R), brain-derived neurotrophic factor (BDNF), nerve growth factor, neurotrophin-3, neurotrophin-4, tropomyosin receptor kinase, and insulin and insulin-like growth factor-1 (IGF-1) and insulin-like growth factor-2 (IGF-2) and their receptors by direct-binding enzyme-linked immunosorbent assay. Results: FTLD brains had significantly elevated pTau, ubiquitin, TGF-β1, and HNE immunoreactivity relative to control. In addition, BDNF and neurotrophin-4 were respectively reduced in BA8/9 and BA38, while neurotrophin-3 and nerve growth factor were upregulated in BA38, and tropomyosin receptor kinase was elevated in BA24. Lastly, insulin and insulin receptor expressions were elevated in the frontal lobe, IGF-1 was increased in BA24, IGF-1R was upregulated in all three brain regions, and IGF-2 receptor was reduced in BA24 and BA38. Conclusions: Aberrantly increased levels of pTau, ubiquitin, HNE, and TGF-β1, marking neurodegeneration, oxidative stress, and neuroinflammation, overlap with altered expression of insulin/IGF signaling ligand and receptors in frontal and temporal lobe regions targeted by FTLD. Dysregulation of insulin-IGF signaling networks could account for brain hypometabolism and several characteristic neuropathologic features that characterize FTLD but overlap with Alzheimer's disease, Parkinson's disease, and Dementia with Lewy Body Disease.